“It's disappointing and it's pretty frustrating, because it feels like it's something that will never go away.” A qualitative study exploring individuals’ beliefs and experiences of Achilles tendinopathy - Jeffrey Turner (341283) (2020)
Background Achilles tendinopathy (AT) is a common and often persistent musculoskeletal disorder affecting both athletic and non-athletic populations. Despite the relatively high incidence there is little insight into the impact and perceptions of tendinopathy from the individual’s perspective. Increased awareness of the impact and perceptions around individuals’ experiences with Achilles tendinopathy may provide crucial insights for the management of what is often a complex, persistent, and disabling MSK disorder. Purpose To qualitatively explore the lived experiences of individuals with AT. Design A qualitative, interpretive description design was performed using semi-structured telephone interviews. Methods Semi-structured interviews were conducted on 15 participants (8 male and 7 female) with AT. Thematic analysis was performed using the guidelines laid out by Braun and Clarke. The study has been reported in accordance with the consolidated criteria for reporting qualitative research (COREQ) checklist. Results Four main themes were identified from the data: 1) beliefs and perceptions surrounding AT: “If I'm over training or something, I don't really know”, 2) the biopsychosocial impact of AT: “I think it restricts me in a lot of things that I would be able to do”, 3) individuals’ experiences with the management process: “You want it to happen now. You're doing all this stuff and it's just very slow progress”, and 4) future prognosis and outlook in individuals with AT: “I see myself better”. Conclusions This study offers a unique insight into the profound impact and consequences of Achilles tendinopathy in a mixed sample of both athletic and non-athletic individuals. The findings of this study have important clinical implications. Specifically, it highlights the need for clinicians to recognize and adopt treatment approaches to embrace a more biopsychosocial approach for the management of tendinopathy. Other Information Published in: PLOS ONE License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1371/journal.pone.0233459